Malachite green adsorption by potassium salts-activated carbons derived from textile sludge: Equilibrium, kinetics and thermodynamics studies - Tang, S. H. (John Wiley and Sons Ltd, 2017)
This work is aimed at evaluating the adsorption of malachite green (MG) on potassium salts-activated carbons derived from textile sludge. Potassium hydroxide (KOH), potassium iodide (KI), and the potassium salts (KOH + KI) composite were used in chemical activation. The physicochemical properties of the activated carbons were characterized according to textural and surface chemistry. The specific surface area of activated carbon is in the range of 66 to 584 m2/g. The KOH and KI + KOH composite series exhibit a higher surface area. The maximum MG adsorption are between 167 and 113 mg/g. Langmuir model shows the best conformity to the equilibrium data, while the kinetics data were best fitted to the pseudo-second-order model, suggesting the chemisorption process. The intraparticle diffusion maybe involved, but it is not the sole rate-limiting step, while the film diffusion could be the controlling mechanism. Thermodynamics data revealed that the MG adsorption is spontaneous and endothermic.